(untitled) (Bangladesh Medical Journal, 2026)
Venous leg ulcer (VLU) is the most advanced manifestation of chronic venous insufficiency and remains a major cause of morbidity, prolonged disability, and healthcare burden worldwide. Although endovenous laser ablation (EVLA) improves ulcer healing by correcting superficial venous reflux, delayed healing remains common in a subset of patients. This study aimed to evaluate factors associated with delayed healing of VLUs following EVLA. This retrospective cohort study was conducted at the Department of Vascular Surgery, Ibrahim Cardiac Hospital & Research Institute, Dhaka, Bangladesh, from January 2020 to December 2024. A total of 256 adult patients with duplex-confirmed venous leg ulcers who underwent EVLA with or without adjunctive foam sclerotherapy were included using consecutive sampling. Delayed healing was defined as failure of complete epithelialization or a <50% reduction in ulcer area within 12 weeks after intervention. Demographic, socio-economic, clinical, mobility-related, and venous variables were analyzed. Univariate and multivariate logistic regression analyses were performed to identify predictors of delayed healing. Odds ratios (ORs) with 95% confidence intervals (CIs) were calculated. The mean age of the participants was 48.16±11.69 years, and 65.6% were male. Hypertension (56.3%), atrial fibrillation (33.6%), diabetes mellitus (32.8%), and coronary artery disease (23.8%) were common comorbidities. Most patients belonged to lower and middle socio-economic groups and demonstrated limited mobility and delayed healthcare-seeking behavior. Significant predictors of delayed healing in univariate analysis included small saphenous vein reflux (OR 2.15; p=0.012), persistent superficial reflux after ablation (OR 5.72; p<0.001), recanalization (OR 5.80; p<0.001), previous deep vein thrombosis (OR 2.21; p=0.015), and wheelchair dependence (OR 2.06; p=0.035). In multivariate logistic regression analysis, persistent superficial reflux after ablation remained the strongest independent predictor of delayed healing (adjusted OR 5.28; p<0.001), while wheelchair dependence also remained significant (adjusted OR 2.10; p=0.027). Other demographic and systemic comorbidities were not statistically significant. Persistent superficial reflux, recanalization, previous DVT, SSV reflux, and impaired mobility are major contributors to delayed healing after EVLA. Early detection of residual reflux, optimized post-procedural surveillance, rehabilitation, and improved socio-economic support may improve healing outcomes and reduce chronic ulcer burden. Bangladesh Med J. 2025 Sept; 54(3): 9-15